PERCEPTION OF KNOWLEDGE CREATION, KNOWLEDGE MANAGEMENT PROCESSES,TECHNOLOGY AND APPLICATION IN MILITARY ORGANISATIONS - Ismail, Manuri; Raja Abdullah, Raja Yaacob (Malaysian Journal of Library and Information Science, 2017)
Current and future warfare depend on sophisticated sensor and imaging technologies and advanced communications and computers which demand the Malaysian Armed Forces (MAF) to develop its ability towards managing the battle space effectively. The development of modern warfare is reflected by the rising importance of having knowledge advantage and information supremacy over adversaries. Leadership, sense-making, problem-solving and decision-making are more complex and more demanding in military situations. Command and control is taking on new dimensions, and the role of military personnel is evolving into that of ‘knowledge force’. A study on military officers of the MAF of , perception towards Knowledge Management (KM) which incorporates knowledge creation, KM processes, technology and applications was conducted in the military environment. The focus of the study is to examine the perceptions of military personnel toward the KM key drivers, which include the people, process, and technology. The results of the study indicated that the demographic elements have influenced over the creation of knowledge, and the applications of KM were influenced by the KM processes and technology infrastructure in the MAF. The innovation of KM in the MAF could be implemented with the right leadership support in line with the aspiration of transformation towardsdeveloping Knowledge Force of the MAF